The IBO germination quantitative trait locus encodes a phosphatase 2C‐related variant with a nonsynonymous amino acid change that interferes with abscisic acid signaling. Issue 3 (9th December 2014) - Amiguet‐Vercher, Amélia; Santuari, Luca; Gonzalez‐Guzman, Miguel; Depuydt, Stephen; Rodriguez, Pedro L.; Hardtke, Christian S.
Summary Natural genetic variation is crucial for adaptability of plants to different environments. Seed dormancy prevents precocious germination in unsuitable conditions and is an adaptation to a major macro‐environmental parameter, the seasonal variation in temperature and day length. Here we report the isolation of IBO, a quantitative trait locus (QTL) that governs c. 30% of germination rate variance in an Arabidopsis recombinant inbred line (RIL) population derived from the parental accessions Eilenburg‐0 (Eil‐0) and Loch Ness‐0 (Lc‐0). IBO encodes an uncharacterized phosphatase 2C‐related protein, but neither the Eil‐0 nor the Lc‐0 variant, which differ in a single amino acid, have any appreciable phosphatase activity in in vitro assays. However, we found that the amino acid change in the Lc‐0 variant of the IBO protein confers reduced germination rate. Moreover, unlike the Eil‐0 variant of the protein, the Lc‐0 variant can interfere with the activity of the phosphatase 2C ABSCISIC ACID INSENSITIVE 1 in vitro. This suggests that the Lc‐0 variant possibly interferes with abscisic acid signaling, a notion that is supported by physiological assays. Thus, we isolated an example of a QTL allele with a nonsynonymous amino acid change that might mediate local adaptation of seed germination timing.